Perception of patient safety culture among nursing students: A cross‐sectional study - Carmen Amaia Ramírez‐Torres; Félix Rivera‐Sanz; Ana Cobos‐Rincon; Teresa Sufrate‐Sorzano; Raúl Juárez‐Vela; Vicente Gea‐Caballero; Clara Isabel Tejada Garrido; Maria Estela Colado Tello; Angela Durante; Iván Santolalla‐Arnedo (Wiley, 2023)
Abstract Aim To analyse the perception of patient safety culture among nursing students and to compare patient safety outcomes between the different year nursing groups. Design A cross‐sectional descriptive study was conducted with nursing students (n = 266) between first and fourth years from one university in Spain. Methods The project was conducted during the 2020/21 academic year. The data were collected using a translated and adapted version of the "Hospital Survey on Patient Safety" developed by the Agency of Healthcare Quality (AHQR). Results Significant differences were found between the year of study of the nursing degree and whether or not specific training in patient safety culture had been received. The nursing students who had received specific training gave scores lower than anyone else in all questionnaire items, but only the indicators of "good practice" (p = 0.00) and "frequency of reported events" (p = 0.0012) showed significant differences. In some cases, fourth‐year students had lower significant mean scores in their "perception of patient safety within unit/sector," "indicators of good practice" and "total score." Public Contribution Adverse events related to clinical practice continue to be a global problem. Improvements in patient safety require an increase in the patient safety culture of professionals and the promotion of development facilitators. Clinical practice and specific theoretical training foster greater awareness and demand related to patient safety, which is of interest when it comes to the development of new programmes that combine both methodologies and improve their effectiveness. Patient safety will continue to be a focus for all healthcare systems. The patient safety culture of future healthcare professionals should be developed at the university level in order to avoid unnecessary adverse events.